English Phonological Interference in Arabic Language Learning: A Systematic Literature Review - Muhammad Fariq Heemal Attruk Attruk; Dika Ayu Solihah (Universitas Kristen Cipta Wacana, 2026)
This systematic literature review investigates phonological interference from English into Arabic, an area that has received far less scholarly attention than interference in the opposite direction. The review was designed to identify the major types of phonological interference experienced by native English-speaking learners of Arabic, determine which Arabic phonological features are most affected, examine the research methodologies commonly used in previous studies, and analyze the pedagogical implications reported in the literature. Following the PRISMA 2020 guidelines, a systematic search was carried out in the Scopus database and produced 189 records. After the screening process, eight peer-reviewed journal articles and conference proceedings published between 2010 and 2026 fulfilled the inclusion criteria. Data extraction was conducted independently by two reviewers, and the risk of bias was evaluated using six methodological criteria. The findings were synthesized through narrative and thematic analysis. The review revealed that phonological interference mainly occurs in three forms: perceptual difficulties in distinguishing Arabic consonant contrasts that do not exist in English, production-related errors such as geminate hypoarticulation and covert contrast, and orthographically mediated errors associated with the deep orthography of Arabic. Among the phonological features examined, emphatic consonants, gemination, and short vowels emerged as the most vulnerable to interference. The studies reviewed primarily employed perception experiments, production experiments, corpus-based error analysis, and quasi-experimental approaches. The pedagogical implications highlighted most consistently across the studies include the importance of explicit phonological instruction, the consistent use of diacritics, the integration of acoustic tools such as PRAAT, and the development of learning environments that provide rich authentic input. Overall, these findings offer a comprehensive synthesis of current research on English-to-Arabic phonological interference and provide an empirical basis for developing Arabic language teaching materials and curricula that are more responsive to the needs of native English-speaking learners.